The Generalized Maximum Angle Condition for the Q1 Isoparametric Element (Journal of Computational Mathematics, 2018)
We consider the quadrilateral $Q$1 isoparametric element and establish an optimal error estimate in $H$1 norm for the interpolation operator under a weaker mesh condition which admits anisotropic quadrilaterals and allows the quadrilateral to become a regular triangle in the sense of maximum angle condition [5,11].
Keywords: Quadrilateral mesh; $Q_{1}$ isoparametric element; Generalized maximum angle condition.